1996
DOI: 10.1093/jat/20.4.266
|View full text |Cite
|
Sign up to set email alerts
|

Two Fatal Cases of Venlafaxine Poisoning

Abstract: Venlafaxine is a phenethylamine derivative that has recently been approved for use in the treatment of depression. It is chemically unrelated to tricyclic, tetracyclic, or other available antidepressant agents. Anticholinergic, hypotensive, hypertensive, and cardiotoxic side effects are rare. Two fatal cases encountered at separate laboratories are discussed, both involve high levels of venlafaxine. Concentrations of the drug in peripheral blood, heart blood, urine, vitreous humor, and liver are reported. Desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…In addition, widening of the QRS interval has been seen in some patients [Kokan and Dart, 1996]. There have been only a few reports of death associated with venlafaxine overdose and the mechanisms underlying these fatalities are unclear [Parsons et al, 1996;Jaffe et al, 1999]. To understand the cardiovascular properties of venlafaxine, Khalifa et al [1999] examined its effects on the inward I Na current, which is the major depolarizing current involved in impulse propagation within the ventricles.…”
Section: Cardiovascularmentioning
confidence: 99%
“…In addition, widening of the QRS interval has been seen in some patients [Kokan and Dart, 1996]. There have been only a few reports of death associated with venlafaxine overdose and the mechanisms underlying these fatalities are unclear [Parsons et al, 1996;Jaffe et al, 1999]. To understand the cardiovascular properties of venlafaxine, Khalifa et al [1999] examined its effects on the inward I Na current, which is the major depolarizing current involved in impulse propagation within the ventricles.…”
Section: Cardiovascularmentioning
confidence: 99%
“…There was also no significant difference in the result if drugs were categorized according to drug type (SSRI, SNARI and antipsychotic) or results for all drugs were tested together in one group. If results from previously published studies were also included, correlations still did not reach significance [8][9][10][11][12][13][18][19][20][21].…”
Section: Effect Of Physiochemical Properties and Extend Of Redistribumentioning
confidence: 96%
“…It was suggested that the drugs were administered in hospital and the differences in concentration between the two specimens were most likely a result of incomplete absorption. In the two studies in which post-mortem peripheral and central blood venlafaxine and metabolite concentrations were compared, central blood concentrations were approximately 1.5-2 times those found in peripheral blood [8,9,12].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several methods have been described to determine venlafaxine in biological fluids [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The techniques used include CE with UV and MS detection [7][8][9][10][11][12], GC [13][14][15] and HPLC with UV [16][17][18], MS/MS [19], coulometric [20], electrochemical [21] and flourimetric [22] detections. Makhija and Vavia have studied the stability of venlafaxine by HPLC [18], without characterizing the products of degradation.…”
Section: Introductionmentioning
confidence: 99%